Batch fermentation of recombinant Escherichia coli producing β-glucuronidase using different control condition - Abdul Karim, Mohamed Ismail; Mohd. Salleh, Hamzah; Mel, Maizirwan (IIUM Press, 2011)
Expenments were carried out in batch process in bioreactor to study the growth kinetics of E coli at different control condition. The process condition has been designed using Taguchi's method with three factors and two levels. From four experiment, Run 1 which has the condition of p02=40%, airflow rate=0.5 vvm and pH=7.2 produce the highest product yield, Yp/s of 1.03 (g/g) and the smallest specific growth rate, u of 0.0072 h-1.